Pengaruh Iradiasi Terhadap Enzim Buah Pisang (Musa paradisiaca) - Aryanti Aryanti; Ermin Winarno; Nurhidayati Nurhidayati; R. Sinaga (agriTECH, 1994)
The purpose of this study was to investigate the effect of irradition on the activity of pectinesterase, peroxisidase, polyphenol oxidase enzymes and their isoenzymes respectively. Bananas were irradiated at the doses of 0; 0,15; 0,3 and 0,45 kGy.and stored at 22°C and RH 70 - 80%. The results showed that irradition at the dosis of 0,15; 0,3 and 0,45 kGy could reduce pectinesterase activity by 4.52; 16.96 and 18.57% respectively. The activity of peroxidase were reduce by irradiation at the doses of 0,3 and 0,45 kGy by 16.37 and 21.81% and polyphenoloxidase were 19.67 and 24,52% lower than the control. The intensity of irradiated samples were lower than those of control. Irradiation doses of 0,3 kGy could be used to prolong the shelf-life of bananas up to three weeks; the firmness, L, a and b values of this irradiation level were higher than those of the control, and those of the irradiated at the doses of 0.15 and 0.45 kGy up to two weeks.